Sustainable use of forest resources and bio-energy for mitigating and adapting climate change. Finnish –Japanese Forest Seminar. Abstracts and Conclusions. Joensuu, Finland, 7 –9 September 2009 - (:unkn) unknown (Finnish Forest Research Institute, 2010)
This issue of Metla s Working Papers is a compilation of the abstracts and presentations of the first Finnish Japanese Forest Seminar on Sustainable use of forest resources and bio-energy for mitigating and adapting climate change held in Joensuu, Finland from 7 9 September 2009. The main goal of the seminar was to discuss the impacts of climate change on forest recourses, the adaptation of forests to climate change and their contribution to mitigation.The forest seminar was a great success, increased the general knowledge base on climate change issues of both countries and helped Finnish and Japanese researchers to create a new research network or to deepen already existing relations. Altogether 30 participants from the Finnish Forest Research Institute (Metla), the Japanese Forestry and Forest Products Research Institute (FFPRI), Nagasaki University, the University of Tokyo, the Japan International Research Center for Agricultural Sciences (JIRCAS), the Advanced Industrial Science and Technology Biomass Technology Research Centre (BTRC-AIST) Japan, Finnish Wood Research Oy and the Seinäjoki University of Applied Sciences participated in the first seminar.Timely and important topics have been chosen for the next Finnish Japanese Forest Seminar organized by FFPRI in autumn 2010 in Japan. The seminar will focus on three main issues: ecosystem services and public goods; physical and chemical properties of wood; and promoting private forestry. The preparations are already underway. The Academy of Finland financed the publication of this issue.
Keywords: bioenergia; metsien kestävä käyttö; ilmastonmuutokset; bioenergy; climate change; sustainable use of forests